2003
DOI: 10.1007/s00261-001-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

Value of CT after laparoscopic repair of postsurgical ventral hernia

Abstract: Preliminary results suggest that CT is a useful imaging tool in patients with laparoscopic repair of incisional vetral hernia. It showed the correct site of the mesh, subclinical fluid collections in the abdominal wall, and recurrent hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Radiologic imaging can be used to establish the right diagnosis. The use of CT-scans to distinguish between bulging or recurrence can be challenging because polypropylene meshes are visible lines with densities similar to adjacent muscle and can better be identified with ultrasound [10] , [11] , [12] . When performing surgical repair for symptomatic bulging it is often not necessary to remove the implanted mesh when incorporation is sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologic imaging can be used to establish the right diagnosis. The use of CT-scans to distinguish between bulging or recurrence can be challenging because polypropylene meshes are visible lines with densities similar to adjacent muscle and can better be identified with ultrasound [10] , [11] , [12] . When performing surgical repair for symptomatic bulging it is often not necessary to remove the implanted mesh when incorporation is sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…This method is limited to the assessment of adhesions at the anterior abdominal wall; the whole abdominal and pelvic cavity cannot be investigated, and the thin prothetic mesh material itself cannot be assessed at all because of the lack of echogenic properties [22]. On CT images the ePTFE mesh can be delineated directly like in our MR studies [23]. CT can also demonstrate typical adhesion-related complications like hernia recurrence, seroma or strangulated obstruction or bowel ischemia [24,25].…”
Section: Introductionmentioning
confidence: 95%
“…In this sense our study seeks to provide a new concept in the imaging diagnosis and treatment of the laparoscopic abdominal wall hernias. It is true that the CT studies, both in the pre and postoperative course, have been useful [10] [11] and recommended [5], but only some MRI studies have been reported by the radiologists in the diagnosis of both inguinal and incisional hernias [4] [12] [19].…”
Section: Discussionmentioning
confidence: 99%